Failure is impossible : Susan B. Anthony in her own words - Sherr, Lynn.; Anthony, Susan B. (Susan Brownell), 1820-1906. (New York : Times Books, 1995)
Susan Brownell Anthony's birthdate has its 175th anniversary in 1995, which is also the 75th year since passage of the 19th Amendment gave women the right to vote. There couldn't be a better time to remember the inspirational words of the woman who, more than any other individual, is responsible for the crusade for women's equality. Anthony's life was her work, a life of action to inspire change. Raised a Quaker, she developed a strong sense of social responsibility that drew her both to the abolitionist movement and to the suffragist cause. A tireless campaigner into her eighties (although she did not live long enough to see women get the vote), she not only helped change laws but changed attitudes and introduced the entire realm of equal rights for women to a very reluctant nation. At first ridiculed, she was ultimately welcomed into the White House and cheered in Congress.
Anthony's legacy goes far beyond the vote. Eloquent, visionary, and armed with a trenchant wit, she addressed many crucial issues - equal opportunity, political representation, domestic violence, and financial autonomy - that remain at the forefront of feminism. In researching the women's movement, writes Lynn Sherr, "I learned that Anthony and her colleagues had not only gotten there first, and said it better, but that they had carefully, wittily, and sometimes painfully laid the groundwork for virtually every right we were either demanding or already took for granted."
Includes bibliographical references (p. [369]-370) and index.
Keywords: Anthony, Susan B. -- 1820-1906.; Feminists -- United States -- Biography; Suffragists -- United States -- Biography